2005
DOI: 10.1007/s10784-005-3808-5
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Global Environmental Facility (GEF) in China: Achievements and Challenges as Seen by the Chinese

Abstract: achievements, challenges, China, Chinese perceptions, effectiveness, GEF, implementing agencies, UNDP, UNEP, World Bank,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…We hypothesize that developing country governments may have reacted to the financial opportunity provided by the Clean Development Mechanism (CDM), see von Stein (2008), and to RE-related capacity building under development and environmental finance initiatives (Heggelund et al, 2005). While reacting to the CDM would imply a form of incentive-based policy diffusion mechanism such as the one observed by Welch and Thompson (1980) or Daley and Garand (2005), the effects of capacity building would rather resemble learning.…”
Section: External Determinants Of Policy Adoption In Developing Countmentioning
confidence: 99%
“…We hypothesize that developing country governments may have reacted to the financial opportunity provided by the Clean Development Mechanism (CDM), see von Stein (2008), and to RE-related capacity building under development and environmental finance initiatives (Heggelund et al, 2005). While reacting to the CDM would imply a form of incentive-based policy diffusion mechanism such as the one observed by Welch and Thompson (1980) or Daley and Garand (2005), the effects of capacity building would rather resemble learning.…”
Section: External Determinants Of Policy Adoption In Developing Countmentioning
confidence: 99%
“…80 In this case study, with these fiduciary and safeguard arrangements, the Bank sought to maintain the political, social and environmental integrity of its projects. At the same time, the Ningbo/Cixi government became better informed of the externalities that a developmental project may create and possible mitigation strategies, thus resulting in better local environmental governance.…”
Section: Discussionmentioning
confidence: 99%
“…13 Some World Bank experts suggested that solving China's institutional challenges in environmental management is more critical than overcoming technical and economic challenges. 14 In terms of policy formulation and policy implementation, 15 as Abigail Jahiel documented, the sustainability of successful programmes were shortened by renewed economic reform initiatives in the 1990s. 16 Richard Sanders additionally emphasised that it was market liberalisation, rather than the handicapped state environmental organisations, that poses as an imminent threat to effective environmental protection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 The projects are expected to be sustainable after the financing ceases, which clearly will not always be the case for climate change mitigation projects. FORM OF REVIEW?…”
Section: The Global Environmental Facilitymentioning
confidence: 99%